Use of indole-3-acetic acid (IAA) in postharvest cajá-manga (Spondias dulcis) - Da Silva, Franciele Cristian [UNESP]; Santana, Hygor Amaral; De Menezes, Juliana Oliveira Silva; Tavares, Mírian Carvalho; Martins, Rodolfo David; Siqueira, Ana Paula Silva (Universidad Pedagogica y Tecnologica de Colombia, 2020)
The cajá-manga (Spondias dulcis Parkinson) is an exotic fruit originally from the Polynesian islands. It is a climacteric fruit with a very short postharvest shelf-life as the result of rapid ripening. This study aimed to evaluate the effect of auxin concentrations on delaying the ripening process in cajá-manga fruits. One hundred and twenty cajá-manga fruits were obtained from Hidrolândia-GO, Brazil (16°55’32.35” S and 49°21’39.76” W). A completely randomized design with a 5×2+2 factorial scheme was used. Five indole-3-acetic acid (IAA) concentrations (0, 50, 100, 150 and 200 mg L-1), two evaluation days (5 and 10 days after IAA applications), and two additional treatments (ripe and unripe fruits) were evaluated. Evaluations were carried out every 5 days, in triplicate. The physicochemical variables pulp firmness, titratable acidity, soluble solids, ascorbic acid content, and color of pulp and peel were evaluated. The concentrations 50 and 100 mg L-1 of IAA presented the best results, causing a delay in ripening and the lowest sensory losses in the cajá-manga fuits.
Uso de indol-3-ácido (IAA) en poscosecha de cajá-manga (Spondias dulcis)
Keywords: auxin; Spondias cytherea; storage; vegetable hormone